Obliteration of Recurrent Large Dentigerous Cyst Using Bilateral Buccal Fat Pad Sling Flaps. Issue 5 (July 2016) - Choi, Hwan Jun; Lee, Jun Beom
Abstract : Abstract: Dentigerous cyst (DC), also known as follicular cyst, is an odontogenic cyst with fluid accumulation between the crown and enamel organ of an unerupted tooth, pushing the crown away from the alveolar bone. The patients with DC in the maxillary sinus should be evaluated thoroughly by extraoral and intraoral examinations, proper diagnostic imaging procedures, and pathologic examination to avoid misdiagnosis of maxillary sinusitis. The standard treatment for DC in the maxillary sinus is often removed by Caldwell–Luc approach. Furthermore, marsupialization or functional endoscopic sinus surgery may be performed because of the size, location of the cysts, or the age of the patients. Sometimes, DC recurred and it made contour deformity. The buccal fat pad (BFP) was mentioned for the first time by Heister in 1732 and better described by Bichat in 1802. Egyedi was the first to report use of the BFP in oral reconstruction for the closure of oroantral and oronasal communications, and Tideman et al showed there was no need to cover BFP by a skin graft when used for defects of oral cavity. So, the authors report our experience with the bilateral pedicled sling BFP flap for intraoral reconstruction after larger recurrent DC removal and describe advantages, operative procedure, and possible complications of the DC.